Ultrafast Synthesis of Metal-Layered Hydroxides in a Dozen Seconds for High-Performance Aqueous Zn (Micro-) Battery - Li, Xiangyang; Chen, Fangshuai; Zhao, Bo; Zhang, Shaohua; Zheng, Xiaoyu; Wang, Ying; Jin, Xuting; Dai, Chunlong; Wang, Jiaqi; Xie, Jing; Zhang, Zhipan; Zhao, Yang (Nano-Micro Letters, 2023)
Efficient synthesis of transition metal hydroxides on conductive substrate is essential for enhancing their merits in industrialization of energy storage field. However, most of the synthetic routes at present mainly rely on traditional bottom-up method, which involves tedious steps, time-consuming treatments, or additional alkaline media, and is unfavorable for high-efficiency production. Herein, we present a facile, ultrafast and general avenue to synthesize transition metal hydroxides on carbon substrate within 13 s by Joule-heating method. With high reaction kinetics caused by the instantaneous high temperature, seven kinds of transition metal-layered hydroxides (TM-LDHs) are formed on carbon cloth. Therein, the fastest synthesis rate reaches ~ 0.46 cm2 s−1. Density functional theory calculations further demonstrate the nucleation energy barriers and potential mechanism for the formation of metal-based hydroxides on carbon substrates. This efficient approach avoids the use of extra agents, multiple steps, and long production time and endows the LDHs@carbon cloth with outstanding flexibility and machinability, showing practical advantages in both common and micro-zinc ion-based energy storage devices. To prove its utility, as a cathode in rechargeable aqueous alkaline Zn (micro-) battery, the NiCo LDH@carbon cloth exhibits a high energy density, superior to most transition metal LDH materials reported so far. Highlights: 1 An efficient and general strategy for ultrafast synthesis of seven transition metal layered hydroxides on conductive substrates is proposed, which avoids the use of additional reagents, multiple steps and long production time in the traditional bottom-up method. 2 The whole synthesis process only takes as fast as approximately 13 s, and its synthesis rate reaches ~ 0.46 cm2 s−1. 3 The NiCo LDH@CC as a demonstration example is selected as cathode material for aqueous alkaline Zn (micro-) battery, which exhibits an outstanding performance.